Serum oxidative stress is an independent prognostic marker in colorectal cancer - Sugimoto, Kiichi; Sakamoto, Kazuhiro; Kawai, Masaya; Kawano, Shingo; Munakata, Shinya; Ishiyama, Shun; Takahashi, Makoto; Kojima, Yutaka; Tomiki, Yuichi (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Few previous studies have investigated the relationship between serum oxidative stress and the status of patients with colorectal cancer. Our aim in the current study was to investigate the significance of serum oxidative stress as a prognostic marker in these patients. Methods: The subjects were 53 patients who underwent curative resection of high-risk stage II or stage III colorectal cancer. The correlation of serum oxidative stress (Reactive Oxygen Metabolites Test: d-ROMs Test) with recurrence-free survival was examined. Results: There were no significant differences in d-ROMs between the recurrence and non-recurrence groups at four time points (0M: before the start of postoperative adjuvant chemotherapy; and 1M: 1 month; 3M: 3 months; and 6M: 6 months after the start of postoperative adjuvant chemotherapy). Only the 3M/0M d-ROMs (the value at 3M relative to the value at 0M) was increased compared with the other time points in the recurrence group, as well as with all time points in the non-recurrence group. In univariate analysis, there were significant differences in recurrence-free survival with respect to N classification (P=0.004) and 3M/0M d-ROMs (P=0.002). In multivariate analysis, both N classification and serum oxidative stress were found to be significant independent prognostic factors (P=0.02, HR=4.49; P=0.02, HR=5.61, respectively). Conclusions: The results of this study demonstrate the prognostic value of serum oxidative stress in colorectal cancer.